An ozone climatology: relationship between meteorology and ozone in the Southeast USA. (20th April 2005) - O'Connor, James R.; Roelle, Paul A.; Aneja, Viney P.
A statistical analysis of ozone (O3 ) concentrations and meteorological parameters was performed to determine the relationship between meteorological changes and ambient O3 concentrations in the Southeast United States. The correlation between average daily maximum O3 concentration and various meteorological variables was analysed on a monthly basis from April through October during 1980-1994. The correlations were strongest during the summer months, particularly June, July, and August. Analysis of long term O3 concentration trends indicates increasing trends during the 1980s and decreasing trends during the early 1990s.